PERAN TENAGA KERJA WANITA HOME INDUSTRI BATIK DAN KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA DI DESA MOJOSARI KECAMATAN KAUMAN KABUPATEN TULUNGAGUNG - Mur Agni Septia; Arfida Boedirochminarni; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2017)
The aim of this research is to know the profile and female labors’ contribution and to know the influence of age, number of products and training female home industry labors’ income in Mojosari. The research method is multiple linear regression and simple income calculation. The result of this research is the majority of respondents are at the age of 61 - 70 years old, meanwhile, the respondents’ education is elementarily graduated. The result of female labors’ income contribution is 25.63% of total family income, so the female labors’ contribution as batik craftsman is still relatively low. The regression test shows variables of age, number of products and training are influencing and significant toward the female labors’ income simultaneously, meanwhile in partial, age has negative correlation and significant, number of products is positively influence and significant and training is positively influence and significant toward female labors’ income.Keywords: Females’ income, Contribution, Age, Number of product, Training